Land Use Law: Marred by Public Agency Abuse - Rodney L. Cobb (Washington University Journal of Law & Policy, 2000)
This Essay is written by an advocate for land use planning and focuses on how these abuses by public agencies impact on public interest planning programs and ultimately on all private interests.
Keywords: Government agencies; Land use; Regional planning